Experimental mathematics – several remarks from historian of science - Maślanka, Krzysztof (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2015)
The paper deals with the ever growing role of computers in pure mathematics. Several examples, mainly from number theory, when numerical experiments did shed some light on difficult problems are given.